Exploring Foreign Direct Investments and engagements of socialist Multinational Enterprises: A case study of Skoda works in the 1970s and 1980s - Markéta Malá (Charles University in Prague, Institute of Economic Studies (IES), 2024)
This paper explores foreign engagements of socialist enterprises in non-socialist countries during the late stage of socialism in Central Europe. It shows that, contrary to popular belief, phenomena such as Foreign Direct Investment (FDI) and Multinational Enterprises (MNEs) were relevant in the context of former socialist countries. Using éSkoda Works as a case study and drawing upon previously unused archival data, this paper outlines an alternative model of international expansion of firms that prioritizes securing future export markets over the typical capitalist focus on equity and profit. This paper also highlights country-level differences of Skoda Works' activities, the bonuses tied to export quotas and profit targets incentivizing managers to pursue foreign activities, or the considerable autonomy of the enterprise in its foreign operations despite the overarching control of the socialist state, which influenced its activities through high-level bilateral agreements, financing, and foreign exchange targets. By employing the approach of a detailed case study placed within the broader context of the era and the region, the paper contributes to a more comprehensive and nuanced understanding of the subject and it enriches the predominantly Hungaryand Poland-focused literature with insights from Czechoslovakia. Additionally, the paper contributes to the ongoing critical debate on the challenges and impacts associated with the operations of international businesses and offers valuable perspectives for future research in this area.
Keywords: F23; N74; N84; P31; 330; International Business under Socialism; Foreign Direct Investment (FDI); Socialist Multinational Enterprises (MNEs); Socialist Central Europe; Non-equity Foreign Operations; Skoda Works